Isolation of pigmented marine bacteria and evaluation of their antibacterial and antioxidant activities against multidrug-resistant bacterial pathogens (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2025)
The present study focused on isolating pigmented marine bacteria and evaluating their antibacterial and antioxidant activities. A total of 12 bacterial strains were isolated from marine sediment samples, among which only PB4, PB5, PB9, PB10, and PB11 produced pigments. Primary antibacterial screening revealed that PB5 and PB10 exhibited antagonistic activity against multidrug-resistant bacterial pathogens. In secondary screening, the cell-free supernatant of PB5 exhibited the highest inhibition zone (18 mm) against all tested pathogens at a concentration of 100 µL. Consequently, PB5 was selected for further morphological, biochemical, and molecular characterisation. Gram staining and biochemical tests identified the strain as belonging to the genus Bacillus, and 16S rRNA sequencing confirmed it as Bacillus gibsonii (GenBank accession no. OQ608089). Pigment extraction using organic solvents such as methanol, ethanol, ethyl acetate and petroleum ether of varying polarity revealed methanol as the most effective, yielding an orange pigment with the highest antibacterial activity. Methanolic crude pigment showed maximum inhibition against Staphylococcus aureus (24±1.53 mm) and Escherichia coli (22±0.58 mm) at 100 µL. Antioxidant analysis by DPPH assay demonstrated significant radical scavenging activity (229.46±0.3%) with an IC₅₀ value of 45.6 µg/mL. These findings suggest that the orange pigment from Bacillus gibsonii possesses strong antibacterial potential against multidrug-resistant pathogens and notable antioxidant properties.